White adipose tissue and circadian rhythm dysfunctions in obesity : Pathogenesis and available therapies - Pagano, E. S. (2016)
A combined neuroendocrine, metabolic, and chronobiological view can help to better understand the multiple and complex mechanisms involved in obesity development and maintenance, as well as to provide new effective approaches for its control and treatment. Indeed, we have currently updated data on the whole adipogenic process involved in white adipose tissue (WAT) mass expansion, namely due to a mechanism whereby WAT cells become hypertrophic, thus inducing a serious local (WAT) inflammatory condition that in turn, will impair not only the cross-talk between the hypothalamus and the WAT, but also favoring the development of deep and widespread neuroendocrine-metabolic dysfunction. Moreover, we also have revisited the circadian clock genes involved in dysfunctional WAT mass expansion and the mechanisms that may lead to obesity development, including early metabolic dysfunctions, enhanced oxidative stress and distorted energy homeostasis. The epigenetic changes of clock genes driving metabolic disease and obesity development have also been included in this review. Finally, we have also underlined the relevance of metabolic homeostasis regulation by central and peripheral organ clocks, sleep disturbances, nutrients, and feeding time, as key factors in obesity development as well as both, classical and chronotherapeutic approaches for its prevention and treatment.